Reducing Cogging Torque in V-Shaped BLDC Motors: A FEA Simulation Study on the Impact of Skew Angle - Mandasari, Dewi Rianti; Sudiarto, Budi; Amelia, Lia; Suryandi, Asep Andi (Universitas Sebelas Maret, 2024)
This study thoroughly investigated the impact of stator skew angles on cogging torque in V-shape Brushless Direct Current (BLDC) motors, focusing on electric vehicle applications. Using Finite Element Analysis (FEA) with ANSYS Maxwell, the research assessed how variations in stator core skewness affect torque performance, prioritizing the reduction of cogging torque known for inducing undesirable fluctuations during rotor movement, impacting motor smoothness and noise levels. FEA calculations reveal a significant reduction in cogging torque with the introduction of skew angles to the stator core, enhancing motor efficiency. The study introduces novelty by analyzing the magnetic flux distribution resulting from skew angle variations. Simulation results, particularly on no-load characteristics based on D-axis flux linkage data, offer a comprehensive overview of the motor’s response under no mechanical load. Observations showed that D-axis flux linkage values decreased with increasing stator skew angle, indicating a shift in winding angle. This decline in D-axis flux linkage under no-load conditions demonstrates how variations in stator core skew angles impacted magnetic flux distribution, resulting in different values and promoting a more uniform flux linkage waveform. Increased stator core skew angles correlated with reduced flux linkage values, contributing to decreased cogging torque fluctuations and smoother BLDC motor operation.